Selective binding interactions of deramciclane to the genetic variants of human alpha(1)-acid glycoprotein - Fitos, Ilona; Visy, Júlia; Simonyi, Miklós; Mády, György; Zsila, Ferenc (Biochimica et biophysica acta, 2010)
alpha(1)-Acid glycoprotein (AGP) plays a decisive role in the serum protein binding of several drugs.Genetic variants of AGP have different ligand binding properties. The binding of deramciclane (DER), a chiral anxiolytic agent, has been studied on A and F1/S genetic variants of AGP. The effects of DER and reference drugs on the binding of specific fluorescent and circular dichroism (CD) probes of AGP were determined. Dicumarol (DIC) binding was measured by CD and equilibrium dialysis. DER effectively displaced probes bound to variant A, while it was less effective at displacing probes bound to variant F1/S. DER increased the binding and inverted the induced CD spectrum of DIC in the solution of variant F1/S. This phenomenon could not be brought about by the enantiomer of DER. DER has high-affinity binding (K(a)> or =2x10(6) M(-1)) to variant A, while its binding to the variant F1/S is about thirty times weaker. During simultaneous binding of DER and DIC to variant F1/S a ternary complex having about four times higher affinity is formed, in which the opposite chiral conformation of DIC is favored. The binding interactions found prove that AGP can simultaneously accommodate different ligand molecules. Even weakly bound ligands can provoke unexpected allosteric protein binding interactions.